2017
DOI: 10.1089/end.2016.0827
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Postoperative Double-J Stent Placement After Ureteroscopy: Results from the Clinical Research Office of Endourological Society Ureteroscopy Global Study

Abstract: Patient- and procedure-related variables were identified, which may enable an individualized approach to postoperative stenting, resulting in improved clinical outcomes in urologic stone treatment by URS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…In a recent publication Muslumanoglu et al. suggested a patient‐based, individual decision for stent insertion [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication Muslumanoglu et al. suggested a patient‐based, individual decision for stent insertion [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although current guidelines do not recommend routine stent insertion after an uncomplicated URS, urologists tend to apply ureteral stents [12]. In a recent publication Muslumanoglu et al suggested a patient-based, individual decision for stent insertion [2].…”
Section: Discussionmentioning
confidence: 99%
“…165,166 Stenting after procedure Ureteral stenting with a double-J stent is usually practiced after URS or RIRS, especially when UAS is used. It is believed that its use will decrease postoperative complications, 167 and stents will be removed in 3-14 days to minimize the complications. [168][169][170] However, forgotten stents is an important issue, with a report rate of up to 12.5%.…”
Section: Complicationsmentioning
confidence: 99%
“…reported that routine postoperative stenting is not mandatory, even in patients with uncomplicated ureteroscopy for impacted ureteral stones . In contrast, in the CROES large retrospective study, postoperative DJ stent placement in URS treatment was associated with improvement of some clinical outcomes, such as fewer postoperative complications, compared with not stenting postoperatively . Recently, the necessity of postoperative stenting has not been categorical, rather being decided by surgeon's preference.…”
Section: Rirsmentioning
confidence: 99%
“…41 In contrast, in the CROES large retrospective study, postoperative DJ stent placement in URS treatment was associated with improvement of some clinical outcomes, such as fewer postoperative complications, compared with not stenting postoperatively. 42 Recently, the necessity of postoperative stenting has not been categorical, rather being decided by surgeon's preference. Thanks to the development of smaller instruments for ureteroscopic treatment, it has become apparent that the number of patients who do not need postoperative stenting has increased.…”
Section: Postoperative Stentingmentioning
confidence: 99%